European Conference on Cognitive Ergonomics 2021 2021
DOI: 10.1145/3452853.3452867
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Relevance of a Formal Pre-incision Time-out in Surgery

Abstract: Surgical time-outs are designed to promote situation awareness, teamwork, and error prevention. The pre-incision time-out in particular aims to facilitate shared mental models prior to incision. Objective, unbiased measures to confirm its effectiveness are lacking. We hypothesized that providers’ mental workload would reveal team psychophysiological mirroring during a formal, well-executed pre-incision time-out. Heart rate variability was collected during cardiac surgery cases from the surgeon, anesthesiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…High CogL decreases SA by affecting attention, increasing reaction time, and negatively impacting recognition skills 24,103,104 . Measuring overall team CogL through individual team member measurements can show psychophysiological mirroring and dynamic CogL changes occurring during unexpected or expected, task-specific events and provide evidence of effective teamwork 7,24,64,105,106 . Social proximity is a predictor of behavior as it influences the opportunities available for effective teamwork and communication through nonverbal interactions and is suggestive of a shared mental model 33,37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High CogL decreases SA by affecting attention, increasing reaction time, and negatively impacting recognition skills 24,103,104 . Measuring overall team CogL through individual team member measurements can show psychophysiological mirroring and dynamic CogL changes occurring during unexpected or expected, task-specific events and provide evidence of effective teamwork 7,24,64,105,106 . Social proximity is a predictor of behavior as it influences the opportunities available for effective teamwork and communication through nonverbal interactions and is suggestive of a shared mental model 33,37 .…”
Section: Discussionmentioning
confidence: 99%
“…24,103,104 Measuring overall team CogL through individual team member measurements can show psychophysiological mirroring and dynamic CogL changes occurring during unexpected or expected, task-specific events and provide evidence of effective teamwork. 7,24,64,105,106 Social proximity is a predictor of behavior as it influences the opportunities available for effective teamwork and communication through nonverbal interactions and is suggestive of a shared mental model. 33,37 Studies have shown that computer vision techniques and proximity sensors for movement analysis can demonstrate an association between movement and teams with "poor" and "good" SA in the OR.…”
Section: Nontechnical Skillsmentioning
confidence: 99%